KONSEP ADIL DALAM POLIGAMI MEMURUT IMAM SYAFII - Supriyanto, Agus; Setiani, Imas (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
Fair or Justice comes from the word"adl" or "?qlsth " Is literally the word ?Adi" Is an abstract noun that means straightening or sitting straight^ the same or equivalent, balance is in a balanced state. While polygamy Is derived from the Greek *poly* or "Polus" which means a lot. While ??garni" of the word ?gamein" or "gamos" which means marriage or marriage. Thus, the language of the sense that polygamy Is a marriage or a marriage is much more than a wife. The purpose of this study was to determine the extent to which the concept of Justice In polygamy according to Imam Shafi'i and how its implementation. The method used is the research library. The sources of this study Include the classics, books and other sources of internet related directly or indirectly to the subject of this study. The results of this study Is to determine the meaning of justice in polygamy. Fair in its implementation that includes fair and unseen that have been adapted to the principles of the Quran and the laws In force In Indonesia. In this case the opinion of Imam Shafi'i stated that then expanded again with the opinions of other scholars to achieve maximum results on thisstudy